Chinese international students in a Canadian private secondary school: becoming flexible citizens?. Issue 6 (18th August 2021) - Wu, Xi; Tarc, Paul
ABSTRACT: This study employs the notion of 'flexible citizenship, ' to examine how national and transnational forces and discursive logics mediate Chinese international secondary school students' educational routes and life trajectories. It draws upon a larger ethnographic research programme that followed 11 Chinese students in a Canadian international secondary school across a period of 14 months. Our current findings affirm that neoliberal logics mediated by (trans)national cultural forces shape how participants navigate their lives. In employing flexible citizenship as a lens, we seek to support more comprehensive understandings of Chinese international students as agentic and socially regulated citizens-in-the-making in their transnational routes. More comprehensive understandings, in turn, elicit pedagogical insights on how study abroad might better support the education and wellbeing of (Chinese) students studying internationally.